Effects of Noncontingent Social Interaction on Immediate and Subsequent Engagement in Vocal and Motor Stereotypy in Children With Autism. (May 2014) - Enloe, Kimberley A.; Rapp, John T.
This study evaluated the effects of noncontingent social interaction (SI) on immediate and subsequent engagement in vocal and motor stereotypy in three children with autism. During SI, a therapist delivered continuous interaction in the form of reading aloud from a Kindle™ e-reader. Results showed that when compared with a no-interaction baseline sequence, SI decreased immediate engagement vocal stereotypy for all three participants without increasing subsequent engagement for any participant. Furthermore, SI also increased immediate engagement in motor stereotypy for one participant, decreased immediate engagement in motor stereotypy for two participants, but did not increase subsequent engagement in motor stereotypy for any participant. Some clinical implications and limitations of the findings are discussed.